Well Placement Optimization for Fractured Reservoirs: Coupling StoSAG and EDFM. (25th May 2022) - Xu, Jianchun; Guo, Wanhang; Zhou, Wenxin
Abstract : Well placement optimization is a significant task in oil field development which aims to find the optimal well locations by maximizing the net present value (NPV) or other objective function. It is a highly nonlinear problem involving large number of variables. Despite lots of work has been done on conventional reservoirs, the optimization tool for naturally fractured reservoir (NFR) is still rare. Naturally fractured reservoirs represent significant amounts of oil reserves. The well placement optimization for NFR is challenging due to the high heterogeneity of matrix and fracture system. In this work, a computer-aided well placement optimization method is established for NFR based on the recent advances. The two phases flow discrete fracture numerical simulation model, i.e., the embedded discrete fracture method (EDFM) is used to model the natural fractures as its computational efficiency and flexibility to handle fracture. Then, stochastic simplex approximate gradient (StoSAG) is employed to obtain the approximate gradient by combing the EDFM. The steepest ascent algorithm is used to find the optimal well placement. A series of numerical case studies are set up to examine the performance of the proposed approach. The NPV for water flooding naturally fractured reservoir production optimization substantially increased by using StoSAG.